Measuring Chinese negative emotion towards climate change: Psychometric properties of the Chinese version of Climate Change Anxiety Scale - Sam SS Lau; Kubi Appiah; Cherry CY Ho; Marco CH Cheng; Bo-Yi Yang (The Journal of Climate Change and Health)
Introduction: In response to growing concerns over negative emotions towards climate change worldwide, it is essential that a validated and reliable scale is available for the generalizability of the constructs being measured, and it is not just applicable to Western context, but also the East. Method: The present study aims to conduct a psychometric investigation of the 13-item Climate Change Anxiety Scale (CCAS) of Clayton and Karazsia in Traditional Chinese using a large sample (N = 1,567) of Chinese individuals in Hong Kong, China. The CCAS was translated, back-translated, cross-culturally adapted and pilot-tested. We performed descriptive, scale reliability, exploratory factor and confirmatory factor analyses. Results: Unlike the two-factor structure of the original scale, our results revealed a three-factor structure of the 13-item CCAS version that captured three dimensions of climate change anxiety: intrusive symptoms, reflections on climate anxiety, and functional impairment. The scale showed good goodness-of-fit indices, internal consistency and reliability. The Chinese CCAS version demonstrated high levels of reliability estimates and significant, albeit weak, correlations with the relevant constructs of well-being, anxiety and depression, environmental orientation, self-efficacy and belief denial. Conclusion: Overall, the Chinese CCAS version has good reliability and validity, and it can be used as a valid assessment tool for climate change anxiety screening with Chinese individuals, thus providing a foundation for better understanding various climate change–related emotions through an anxiety lens in the Chinese context.